Novel TBC1D8B variant causes neonatal nephrotic syndrome combined with acute kidney injury - Yuanyuan Xu; Chao Dai; Jing He; Yaping Liang; Ying Zhu; Fang Deng; Chang Wang; Danqun Jin (Italian Journal of Pediatrics)
Abstract Background Nephrotic syndrome (NPHS), characterized by proteinuria, hypoalbuminemia, and edema, can be caused by genetic variations. TBC1D8B was recently discovered as a novel disease-causing gene for X-linked NPHS. With only a few reported cases, the clinical manifestations associated with variants of this gene need to be further examined. Methods We recruited a newborn with NPHS complicated by acute kidney injury (AKI) and his parents and tested the potential genetic cause of the disease through trio-whole exome sequencing and Sanger sequencing. Western blotting (WB) was performed using a mutant plasmid to evaluate mutant protein expression levels. Since the TBC1D8B protein interacts with RAB proteins to catalyze the GTPase hydrolysis process, immunofluorescence (IF) can be used to verify the interaction between the TBC1D8B mutant protein and RAB11A/RAB11B, and thus to confirm its effect on the endocytosis and vesicle recycling functions of RAB proteins within the cell. Results The child, at 1 month, showed severe edema and proteinuria and unexplained coma with epilepsy. Ultrasound examination revealed multiple organ enlargement, and MRI showed nonspecific high diffusion-weighted imaging signal characteristics in the splenium of the corpus callosum. Hematoxylin and eosin staining showed diffuse inflammatory cell infiltration in the renal interstitium and multifocal renal tubule lumen expansion. Diffuse fusion of podocyte foot processes was observed under electron microscopy, indicating glomerular podocyte lesions. Genetic testing revealed a maternally inherited novel hemizygous variant, NM_017752: c.628 A > T, p.Lys210Ter, in TBC1D8B. In vitro functional experiments showed that this variant may lead to TBC1D8B protein degradation. IF results showed disrupted interaction with RAB11A/RAB11B, that then affects the biological function of RAB proteins in the process of cell intimal vesicle formation and intracellular transport. Conclusion This study will enrich the mutational and phenotypic spectra of TBC1D8B and demonstrate the potential of this gene variants to cause early-onset NPHS leading to severe kidney disease.